2019
DOI: 10.1177/002795011924800113
|View full text |Cite
|
Sign up to set email alerts
|

‘High-Skilled Good, Low-Skilled Bad?’ British, Polish and Romanian Attitudes Towards Low-Skilled EU Migration

Abstract: A new skills-based immigration system, with a preference for the highly-skilled, is central to UK policy debates in the Brexit context, arguably responding to majority public opinion on migration. Through qualitative fieldwork with British, Polish and Romanian citizens living in two local authorities in England, this paper shows what participants understand by ‘low-skilled’ and how there is broad support of those who ‘contribute’, but are ‘controlled’ at the same time. Migrants’ narratives of downskilling also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Migration issues (in terms of the culture and values they embody) have primacy in the Brexit discourse. They are often cited to support anti‐immigrant and xenophobic attitudes, nationalism or populism that are associated with the pro‐Brexit vote (Bulat, 2019; Inglehart & Norris, 2016; Rzepnikowska, 2019). The migration question also interacts with different migration patterns of female workers both in comparison with male and between high and low skilled female workers (Bailey & Mulder, 2017; Shutes & Walker, 2018).…”
Section: “Voting With Their Feet” and Other Brexit Hypothesesmentioning
confidence: 99%
“…Migration issues (in terms of the culture and values they embody) have primacy in the Brexit discourse. They are often cited to support anti‐immigrant and xenophobic attitudes, nationalism or populism that are associated with the pro‐Brexit vote (Bulat, 2019; Inglehart & Norris, 2016; Rzepnikowska, 2019). The migration question also interacts with different migration patterns of female workers both in comparison with male and between high and low skilled female workers (Bailey & Mulder, 2017; Shutes & Walker, 2018).…”
Section: “Voting With Their Feet” and Other Brexit Hypothesesmentioning
confidence: 99%
“…Nonetheless, they sound a more general call for expanding notions of 'worthy lives' beyond the 'top half of the income ladder', as Lamont suggests (2018, 432), which is important, given 'low-skilled' migrants' profound and widespread devaluation. Intentions to privilege high-earning 'skilled' migrants in Britain's post-Brexit immigration system are a recent reminder of this devaluation, and enduring skill hierarchies (Bulat 2019). Hagan, Demonsant, and Chávez (2014) criticise similar preferences in US immigration policies, which fail to acknowledge many migrants' abilities and contributions.…”
Section: Resultsmentioning
confidence: 99%
“…Yet, as Hagan, Lowe, and Quingla (2011) point out, such processes of skills development and occupational advancement are often obscured, or typically related to ethnic resources and entrepreneurship, where addressed (see Portes 1998). In the UK too, several studies showed how migrants working in hospitality, domestic or other low-paid sectors could approach their jobs strategically to pursue other (non-economic) aims, develop skills to secure 'good jobs' abroad or at home, and abandon, rather than tolerate, unfavourable conditions (Williams and Baláž 2005;Alberti 2014;Parutis 2014;Bulat 2019). However, the European migrants sampled there are often from specific, usually East European, countries, working in specific sectors, and/or equipped with varying education levels, including university.…”
Section: Skills and Occupational Mobility In The Context Of Migrationmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of clarity, and transparency, in terms of who counts as a 'migrant' results in uncertainty in operationalisation, measurement and analysis and, therefore, the subsequent evidence, its interpretation and the conception of migration the data represents (Anderson and Blinder, 2017;Mateos et al, 2009;Raymer et al, 2019). This has implications as the term 'migrant' is used interchangeably and uncritically in political and public immigration discourses conflating issues of immigration, race, ethnicity, citizenship and asylum, with no recognition of differences in immigration control and policy or legal status, as demonstrated by the focus on EU mobility and concerns over freedom of movement (Anderson, 2017;Anderson and Blinder, 2017;Bulat, 2019;Morrison, 2019). Anderson and Blinder (2017) point out that there is no straightforward mapping of migration data onto the subjects of public debate.…”
Section: Data Sources Definitions and Measurementmentioning
confidence: 99%